The ugly dino hatchling : a graphic novel - Peters, Stephanie True, 1965- (Far out fables, 2018)
In this graphic version of the ugly duckling story, a T-Rex egg falls through a time-portal and is hatched by a mother duck--most of the other animals in the barnyard make fun of Rex (except for one female duckling) but when he saves them from a velociraptor they learn to appreciate his differences.